(untitled) (Comprehensive Journal of Science, 2026)
This study aimed to explore the role of Augmented Reality (AR) technologies supported by Artificial Intelligence (AI) in enhancing the competence of Enterprise Resource Planning (ERP) auditors at the Libyan Court of Accounts. The study problem arises from the limited adoption of interactive modern training technologies within auditing institutions in developing countries, alongside the absence of intelligent training models that consider individual differences and auditors’ levels of professional experience,The study employed a descriptive-analytical survey design, collecting field data using a questionnaire distributed to a convenience sample of auditors at the Libyan Court of Accounts who possess practical experience with ERP systems. Data were analyzed using appropriate statistical methods to assess perception levels and evaluate the impact of interactive training on auditors’ competence,The results indicated a high level of acceptance and positive perception regarding the integration of AR+AI technologies in the auditing work environment. The findings demonstrated that interactive training significantly contributes to meeting professional needs, improving performance, accelerating the learning process, and reducing operational errors. Moreover, statistically significant differences were observed in the evaluation of the effectiveness of these technologies, which were attributed to auditors’ years of professional experience and prior training,The study concluded that transitioning from traditional training models to intelligent interactive learning environments represents a strategic necessity to keep pace with digital transformation requirements in auditing institutions. It recommended adopting training programs based on digital simulations and developing the technical infrastructure of the Libyan Court of Accounts to support the implementation of AI and AR technologies, thereby enhancing the quality and efficiency of financial and administrative auditing practices.